Adapting standards: ethical oversight of participant-led health research. - Effy Vayena (PLoS Medicine, 2013)
As participant-led health research increases, Effy Vayena and and John Tasioulas examine what ethical questions are raised, and what types of standards need to be developed for appropriate ethical oversight for participant-led research projects.